The serum IL-17A levels in patients with traumatic bowel rupture post-surgery and its predictive value for patient prognosis - Zhou Peng; Yu Jie; Yan Bingmei (Open Medicine)
This study aimed to investigate the serum levels of interleukin (IL)-17A in patients with traumatic bowel rupture and its clinical significance, particularly its correlation with inflammatory cytokines, preoperative severity, and postoperative prognosis.